2017
DOI: 10.3758/s13421-017-0738-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of top-down suppression in mitigating the disruptive effects of task-irrelevant feature changes in visual working memory

Abstract: Studies of change detection have shown that changing the task-irrelevant features of remembered objects impairs change detection for task-relevant features, a phenomenon known as the irrelevant change effect. Although this effect is pronounced at short study-test intervals, it is eliminated at longer delays. This has prompted the proposal that although all features of attended objects are initially stored together in visual working memory (VWM), top-down control can be used to suppress task-irrelevant features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 51 publications
3
28
2
Order By: Relevance
“…It is of note that compared with the lifetime of the irrelevant dimension in Treisman and Zhang (2006, 3.0 s), Logie et al (2011, 1.5 s), and Bocincova et al (2017, 1.25 s), the lifetime of the irrelevant dimension in the current study, which is or is not related to biological motion, was much longer. However, caution should be taken in reaching this conclusion as the current study used different materials and indices from the aforementioned two studies.…”
Section: Resultsmentioning
confidence: 49%
See 3 more Smart Citations
“…It is of note that compared with the lifetime of the irrelevant dimension in Treisman and Zhang (2006, 3.0 s), Logie et al (2011, 1.5 s), and Bocincova et al (2017, 1.25 s), the lifetime of the irrelevant dimension in the current study, which is or is not related to biological motion, was much longer. However, caution should be taken in reaching this conclusion as the current study used different materials and indices from the aforementioned two studies.…”
Section: Resultsmentioning
confidence: 49%
“…Logie et al (2011) later conducted a more thorough investigation by manipulating the duration of the delay (0.0, 0.5, 1.0, 1.5, 2.0, and 2.5 s) as well as the type of irrelevant dimension (location, colour, and shape). They found that all the three irrelevant dimension types could be encoded into VWM involuntarily (see Bocincova et al, 2017, for a similar study). Critically, in line with Treisman and Zhang (2006), the distracting effect vanished after a delay period, although the irrelevant location was maintained for a longer time than the irrelevant colour or shape.…”
Section: Experiments 1: the Fate Of Irrelevant Dimensionsmentioning
confidence: 80%
See 2 more Smart Citations
“…This is long enough to rule out short‐lived iconic (sensory) memory as a basis for recall performance in these tasks. However, there is evidence that the effects of task‐irrelevant location changes on change detection performance for feature bindings decline significantly over longer delay durations (Bocincova, van Lamsweerde, & Johnson, ; Logie, Brockmole, & Jaswal, ; Treisman & Zhang, ). It is therefore possible that location is important for feature binding only at short to intermediate delays, and a different storage format supports memory at longer delays.…”
Section: The Role Of Space and Time For Bindingmentioning
confidence: 99%